Comparison of the Appendicular Emptying Velocity of Left Atrium in patient with moderate versus severe chronic rheumatic mitral stenosis measured by pulsed wave Doppler in Transesophageal echocardiography - Bhowmik, Goutom Chandra; Khaled, Md Fakhrul Islam; Parvin, Tanjima; Osmany, DMM Faruque; Haque, Mustashirul; Mostofa, ABM golam; Biswas, Pallob Kumar; Noman, Arifuzzaman; Sumon, Amiruzzaman; Banerjee, Sajal Krishna; et al. (University Heart Journal, 2022)
Background: Left atrial appendage (LAA) is considered the “most lethal human appendage” as it causes significant mortality and morbidity in chronic rheumatic mitral stenosis patients due to cardiogenic cerebral infract. Presence of LAA dysfunction has been shown to be a strong predictor of thrombus formation and the risk of embolic event, even if no clot is found at the time of initial examination. LAA emptying velocity are measured by trans esophageal echocardiography (TEE) represent as a surrogate marker for left atrial(LA) function .LAA emptying velocities (contraction velocity) < 20cm/s are associated with risk of spontaneous echo contrast(SEC), LAA thrombus, and subsequent cardio embolic events. So early detection of low emptying velocity without SEC or LA thrombus can reduce mortality & morbidity related to cardio embolic stroke and also helps in further management procedure like cardio version etc. So we will compare LAA emptying velocity moderate versus severechronic rheumatic mitral stenosis patients in our population for further attention. Objective: To assess emptying velocity of LAA in patient with moderate versus severe chronic rheumatic mitral stenosis, from a Bangladesh health service perspective. Method: This was a cross sectional study which was conducted in UCC, BSMMU during the period of from February 2019 to September 2019 in Echo lab . Study Procedure: We were enrolled 33 CRHD with MS (moderate to severe) patients who underwent TEE and met inclusion & exclusion criteria. The purpose of the study was explained to each subject & informed written consent was obtained. After getting consent relevant history, physical examination and preprocedural investigation was obtained in predesigned structured data collection sheet. TEE was done with Vivid E9® machine. Pulse wave Doppler was position at the tip of the LAA and then emptying velocity of LAA moderate and severe were compared. Outcome measure: Among 33 patients, 3 patients were excluded due to outlier and inadequate data.. In chronic rheumatic mitral stenosis in moderate versus severe cases average LAA emptying velocities were significantly higher moderate CRHD with MS compare to severe CRHD with MS,(26.57±4.91;31.12±5.04), P=0.018. Conclusion:Appendicular emptying velocity of LAA significantly lower in severe CRHD with MS compare to moderate CRHD with MS and it has temporal relation with MS severity. It can be used as a reliable, simple and sami-invasive tool to early predict severity and prevent complication in CRHD with MS as well as for prophylactic measured taken. University Heart Journal 2022; 18(2): 73-79